Awareness and Responsibility of Food Waste Behavior among College Students - Chandra, Alhapen Ruslin; Lita, Ratni Prima; Sari, Dessy Kurnia; Ma ruf, Ma ruf (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
Indonesia is facing a substantial issue of food waste. It contributes to environmental problems and loosens up the economy of the country. This study aimed to investigate the food waste behavior of college students as part of young consumers, because consumer behavior established during youth could influence their behavior in the later stages of life. Based on the Norm Activation Model, the research framework was evaluated using structural equation modelling. The result revealed that college students' awareness of consequences and their ascription of responsibility for food waste had a significant impact on their personal norm, which in turn influenced their intention to prevent food waste. The findings are useful to develop strategies to minimize food waste, particularly among student in higher education institution.